PENGARUH RADIASI ELEKTROMAGNETIK TERHADAP KESEHATAN DAN UPAYA PENCEGAHANNYA - Turnip, Elfrida; Meta Sari, Meta Sari; Hutajulu, Putri Sridewi; Sirait, Yohana; Lubis, Rajo Hasim (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2024)
The impact of electromagnetic radiation on health and preventive measures. Laptops emit electromagnetic radiation, including blue light from screens and microwaves from Wi-Fi modules, which pose potential cumulative health risks. This study aims to measure the electromagnetic radiation emitted by laptops, evaluate its impact on user health, and identify applicable preventive measures. The research employed a qualitative method based on library research with a content analysis approach. The findings reveal that blue light intensity ranges from 10–50 µW/cm², while microwave radiation from Wi-Fi reaches up to 2.0 mW/cm² at close distances. Health impacts include eye fatigue, accommodation disorders, and neurological effects such as headaches and fatigue due to prolonged radiation exposure. Identified preventive measures include blue light filters, screen distance adjustments, and low-power Wi-Fi technology. This study offers practical guidelines to minimize health risks associated with electronic device usage.